Role of green nanomaterials for 3-chloropropane-1,2-diol ester (3-MCPDE) reduction - Syed Putra, Sharifah Shahira; Basirun, Wan Jefrey; Hayyan, Adeeb; Elgharbawy, Amal A.M. (Springer, 2022)
This chapter discusses the promising green nanomaterials synthesis for 3-chloropropane-1,2-diol ester (3-MCPDE) reduction. Toxic chemicals such as 3-MCPDE are classified as potential carcinogen and have been shown to affect kidney function and male fertility. It was reported to be found in food such as soy sauce, bread and baby milk formula. More recently, this compound has been highly found in refined edible oils. One of the techniques to breakdown 3-MCPDE is enzymatic hydrolysis. However, enzymes possess poor reusability and recovery which are often prone to denaturation. Thus, immobilization of enzyme using green nanomaterials is the best technique to enhance the enzymatic activity for reducing 3-MCPDE. Green nanomaterial and green chemistry techniques can play a crucial role in the enzymatic application. This method paves the way for future research to learn more about the effects of green immobilization and their interactions for 3-MCPD reduction which can impact the food industry and hold a great promise for edible oil products with a better quality that is safe to consume by society.